2019
DOI: 10.1136/archdischild-2019-316937
|View full text |Cite
|
Sign up to set email alerts
|

Prelacteal and early formula feeding increase risk of infant hospitalisation: a prospective cohort study

Abstract: ObjectiveTo ascertain the relationship between prelacteal feeding, early formula feeding and adverse health outcomes, especially hospitalisation during the first year of life.DesignMulticentre prospective cohort study.SettingSix hospitals across three cities in Vietnam.PatientsA total of 2030 pregnant women were recruited at 24–28 weeks of gestation and followed up at hospital discharge, 1, 3, 6 and 12 months post partum.Main outcome measuresRates of infant hospitalisation, diarrhoea and lower respiratory trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 23 publications
0
33
0
3
Order By: Relevance
“…3 Adjusted for the mother's education, the mother's pre-pregnancy employment status, birth weight, pacifier used, delivery method, parity, the mother's pre-pregnancy body mass index (BMI), time until the first breastfeed, mother taught how to position and attach, prelacteal feed given, formula given in hospital, infant demand fed at 3 months, infant demand fed at 4 months. 4 Adjusted for the mother's age, the mother's education, the mother's pre-pregnancy employment status, birth weight, pacifier used, delivery method, parity, time until the first breastfeed, mother taught how to position and attach, formula given in hospital, infant demand fed at 1 month, infant demand fed at 3 months, infant demand fed at 4 months. AHR, adjusted hazards ratio; CI, confidence interval; NS, not significant in the adjusted model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Adjusted for the mother's education, the mother's pre-pregnancy employment status, birth weight, pacifier used, delivery method, parity, the mother's pre-pregnancy body mass index (BMI), time until the first breastfeed, mother taught how to position and attach, prelacteal feed given, formula given in hospital, infant demand fed at 3 months, infant demand fed at 4 months. 4 Adjusted for the mother's age, the mother's education, the mother's pre-pregnancy employment status, birth weight, pacifier used, delivery method, parity, time until the first breastfeed, mother taught how to position and attach, formula given in hospital, infant demand fed at 1 month, infant demand fed at 3 months, infant demand fed at 4 months. AHR, adjusted hazards ratio; CI, confidence interval; NS, not significant in the adjusted model.…”
Section: Resultsmentioning
confidence: 99%
“…The explanatory variables examined as potential determinants were derived from the literature and included maternal and infant characteristics such as maternal age, the mother's level of education, the mother's employment status, infant weight, the use of a pacifier; and biomedical and hospital practices, including the method of delivery, parity, body mass index (BMI) before pregnancy, antenatal class attendance, time since birth of the first breastfeed, whether the mother was taught how to attach, whether the infant was given a prelacteal feed of formula while in hospital, and 'feeding on demand' at one, three, and four months [4][5][6] (Supplementary Materials Table S1).…”
Section: Explanatory Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from sub-Saharan African [11,13,15] and Asian [10,16] countries have indicated that inappropriate introduction of complementary foods and bottle feeding were associated with the onset of diarrhoea among infants and young children. This is potentially due to the replacement of irreplaceable human milk by complementary foods and contamination of the food and/or teat/nipple of the bottle [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In a large cohort study ( n = 1709), the prevalence of prelacteal feeding was high (56.5%) and formula feeding was common (79.5%) before hospital discharge. This increased the risks of hospitalisation by 2 months for prelacteal feeds and infant formula use [ 48 ].…”
Section: Introductionmentioning
confidence: 99%